2010
DOI: 10.1111/j.1469-8137.2010.03520.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of carbohydrate metabolism in the ectomycorrhizal fungus Tuber melanosporum

Abstract: Summary• Primary carbohydrate metabolism plays a special role related to carbon ⁄ nitrogen exchange, as well as metabolic support of fruiting body development, in ectomycorrhizal macrofungi. In this study, we used information retrieved from the recently sequenced Tuber melanosporum genome, together with transcriptome analysis data and targeted validation experiments, to construct the first genomewide catalogue of the proteins supporting carbohydrate metabolism in a plantsymbiotic ascomycete.• More than 100 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 65 publications
(128 reference statements)
0
43
0
Order By: Relevance
“…Fruiting body mutants are now available for many fungi other than P. anserina, including Sordaria macrospora [27], N. crassa [28], A. nidulans [29] and Coprinopsis cinerea (formely Coprinus cinereus) [30,31] and could be analyzed using similar methods. They are complementary to the now more widespread large scale analyses of transcriptomes during fruiting body development as performed in the ascomycetes Fusarium graminearum and Fusarium verticilloides [32][33][34], N. crassa [35,36], S. macrospora [37], Pyronema confluens [38], Tuber melanosporum [39][40][41], Cordyceps militaris [42] and Ophiocordyceps sinensis [43], as well as in the basidiomycetes C. cinerea [44], Moniliophthora perniciosa [45], Agrocybe aegerita [46], Lentinula edodes [47,48], Auricularia polytricha [49] and Ganoderma lucidum [50].…”
Section: Resultsmentioning
confidence: 99%
“…Fruiting body mutants are now available for many fungi other than P. anserina, including Sordaria macrospora [27], N. crassa [28], A. nidulans [29] and Coprinopsis cinerea (formely Coprinus cinereus) [30,31] and could be analyzed using similar methods. They are complementary to the now more widespread large scale analyses of transcriptomes during fruiting body development as performed in the ascomycetes Fusarium graminearum and Fusarium verticilloides [32][33][34], N. crassa [35,36], S. macrospora [37], Pyronema confluens [38], Tuber melanosporum [39][40][41], Cordyceps militaris [42] and Ophiocordyceps sinensis [43], as well as in the basidiomycetes C. cinerea [44], Moniliophthora perniciosa [45], Agrocybe aegerita [46], Lentinula edodes [47,48], Auricularia polytricha [49] and Ganoderma lucidum [50].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the presence of a gene coding for a secreted acid invertase has suggested that T. melanosporum is able to hydrolyze sucrose, unlike other ectomycorrhizal fungi, such as Laccaria bicolor (Martin et al 2008(Martin et al , 2010Ceccaroli et al 2011). In addition, transcripts of this gene have been reported to accumulate in the Hartig net compartment, i.e.…”
Section: The Black Truffle Genome Project and The Post-genomic Activimentioning
confidence: 98%
“…These data have improved the T. melanosporum genomic structural annotation and led to the identification of previously unidentified transcripts, exons, untranslated regions (UTRs) that extended in silico gene models and alternative splicing events. In addition, RNA-seq transcript profiling, which provides a global view on the transcriptome complexity, has been used for detailed analyses of specific gene groups (Balestrini et al 2012;Ceccaroli et al 2011;Montanini et al 2011;Rubini et al 2011a). More recently, the functional characterization of novel proteins has been obtained by Islam et al (2013).…”
Section: The Black Truffle Genome Project and The Post-genomic Activimentioning
confidence: 99%
See 1 more Smart Citation
“…The genome sequence of the T. melanosporum black truffle fruiting body suggests that truffles possess all the genes needed to synthesize the key constituents of the truffle aroma (Martin et al 2010), and the Post-Genomics Era has been open to truffle research (Balestrini and Mello 2014;Kües and Martin 2011). Recently, the genomewide transcriptome studies have unraveled several developmental and metabolic pathways regulated by symbiosis and fruiting body formation, as well as environmental factors (Amicucci et al 2011;Bolchi et al 2011;Ceccaroli et al 2011;Montanini et al 2011;Zampieri et al 2011). However, the genes and enzymes involved in the biosynthesis of aroma active compounds, umami amino acids and 5′-nucleotides, and phytosterol are still unclear.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 98%